ITF report: the state of the game 2018 - Capel-Davies, J.; Spurr, J. (Coaching and Sport Science Review, 2019)
In order to fulfil its mission of protecting the nature of tennis and encouraging innovation and improvements, the ITF Technical Centre quantifies the parameters that describe the essence of the sport at the elite level, and thus constitute `the state of the game`. This annual report aims to establish how players, their equipment and the interaction between them are changing over time, to analyse the impact of these changes on the game and to contemplate the merits of any necessary counter-measures. Point length is a key metric of the nature of the game. Too many short points is generally considered unattractive. Low serve returnability can lead to short points, therefore serve returnability should be monitored and understood. Serve returnability is strongly dependent on post-bounce speed, serve angle and the proximity of the bounce to the centre serviceline or sideline. Taller players typically serve faster than shorter players and therefore generate higher post-bounce speeds, lower returnability serves and consequently more short points. The higher post-bounce speed of serves by these players can be reduced, increasing their returnability, by using a slower court and/or larger ball. A warning indicator signalling an excessive number of short points could be used to determine when regulation of equipment might be used to counteract the rise of shorter points. A more radical response would be to make the service-box narrower to increase the returnability of serves without impacting the speed of subsequent shots.